Autoantibodies to post‐translationally modified type I and II collagen in Charcot neuroarthropathy in subjects with type 2 diabetes mellitus. Issue 2 (5th October 2016) - Rizzo, Paola; Pitocco, Dario; Zaccardi, Francesco; Di Stasio, Enrico; Strollo, Rocky; Rizzi, Alessandro; Scavone, Giuseppe; Costantini, Federica; Galli, Marco; Tinelli, Giovanni; Flex, Andrea; Caputo, Salvatore; et al.
Abstract: Aims: Charcot neuroarthropathy (CN) is a disabling complication, culminating in bone destruction and involving joints and articular cartilage with high inflammatory environment. Its real pathogenesis is as yet unknown. In autoinflammatory diseases, such as rheumatoid arthritis, characterized by inflammation and joint involvement, autoantibodies against oxidative post‐translationally modified (oxPTM) collagen type I (CI) and type II (CII) were detected. Therefore, the aim of our study was to assess the potential involvement of autoimmunity in charcot neuroarthropathy, investigating the presence of autoantibodies oxPTM‐CI and oxPTM‐CII, in participants with charcot neuroarthropathy. Methods: In this case‐control study, we enrolled 124 participants with type 2 diabetes mellitus (47 with charcot neuroarthropathy, 37 with diabetic peripheral neuropathy without charcot neuroarthropathy, and 40 with uncomplicated diabetes), and 32 healthy controls. The CI and CII were modified with ribose and other oxidant species, and the modifications were evaluated with sodium dodecyl sulfate‐polyacrylamide gel electrophoresis. Binding of sera from the participants was analyzed with enzyme‐linked immunosorbent assay. Results: Age, body mass index, waist and hip circumferences, and lipid profile were similar across the 4 groups, as well as glycated hemoglobin and duration of diabetes among people with diabetes. An increased binding to both native and all oxidation‐modified forms of CII was found in participants with CN and diabetic neuropathy. Conversely, for CI, an aspecific increased reactivity was noted. Conclusions: Our results detected the presence of autoantibodies against oxidative post‐translational modified collagen, particularly type 2 collagen, in participants with charcot neuroarthropathy and diabetic neuropathy, suggesting the possible involvement of autoimmunity. Further studies are required to understand the role of autoimmunity in the pathogenesis of charcot neuroarthropathy.